Investigation of European Union Horizon 2020 Information and Communication Technology Projects with the Social Network Analysis Method - Sekerci, Deniz; Alp, Selcuk (Engineering, technology & applied science research, 2023)
This study aims to examine the partnerships of the projects accepted in the Horizon 2020 grant support program, which supports innovative Research and Development (R&D) projects of the European Union, using social network analysis according to criteria such as participant countries, the project subjects in which they participate, and the number of funds they receive. Social network analysis can be used in many different areas, as well as in the analysis of collaborations and partnerships. Turkey's partnership has not been examined in detail for such international multi-partner collaborations. While taking advantage of the opportunity to follow the trend of technology by conducting innovative R&D studies with leading organizations in many different strategic fields, the interest and participation rate of Turkey is increasing day by day in such programs, offering opportunities to obtain grant incentives. Examining the network of collaborations established so far in this field can provide various inferences and suggestions for strategic partnerships.